ONLINE SALE OF FASHION GOODS - Jegere, Sarmite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The main channel for the distribution of retail goods is gradually becoming the Internet. It is also a binding distribution channel for the sale of fashion goods. It allows the retailer to take opportunity not only to post photos, video and audio material showcasing their latest collections, but also to sell the goods directly to the consumer through a website. In Latvia, the purchase of goods in the Internet is growing very fast, especially during the Covid - 19 restrictions, when the purchase of goods in stores is restricted. Throughout Europe and especially in Latvia the crisis caused by Covid-19 has led to the questions, such as - what to do now, what should change and what decisions should be made by fashion retailers so that employees and buyers are not so vulnerable in such unpredictable force majeure situations? According to data from the Interactive Media Retail Group, for example, the UK's online retail turnover increased by 42% in September 2020, by 35.7% in October and by 39% in November compared to the previous year. The aim of this article is to analyze researches about online fashion retailers conducted by US and British researchers and the results of surveys among Chinese and Latvian students. The questions included in the researches and surveys are: Who sells fashion items online? Who helps to create a good fashion website? How do fashion retailers design websites? Who buys online? Conclusions and proposals have been made for retail web developers in Latvia.